Impact of management interventions on smallholder dairy farms of the western highlands of cameroon - Bayemi, P. H; Webb, E. C; Ndambi, A; Ntam, F; Chinda, V (Tropical animal health and production, 2009)
A study was carried out to evaluate the impact of interventions to solve constraints in smallholder dairy farms of the Western Highlands of Cameroon. The interventions consisted of improved breeding through introduction of artificial insemination, better feed supplementation, farmers training in milk processing and better veterinary services. Results show that there was a decrease in average monthly expenditures of 18% relative to the month before interventions started. Much of the expenditures were related to feed (38% of all costs). There was an overall increase in farm income. Close to 2/3 of the income were derived from milk products from home processed milk and culled animals. Only 7% income came from milk sold to the processing plant. The partial budget shows that before interventions, farmers lost $4.5/cow/month but gained $38/cow/month because of the interventions. The return was 2.32 and included opportunity income for milk home consumed and shared. When this opportunity income was ignored, the return stood at 1.93. The positive impact of interventions led to poverty alleviation and some farmers acquired more cows. A spill over effect is that more crop farmers are willing to be engaged at least partially in dairy farming. It will be good if many more farmers could benefit from these interventions.